Alterations of the expression levels of CPT-1, SCD1, TRβ-1 and related microRNAs are involved in lipid metabolism impairment in adult rats caused by maternal coconut oil intake during breastfeeding. (December 2019) - Quitete, Fernanda Torres; de Moura, Egberto Gaspar; Peixoto, Thamara Cherem; Torsoni, Adriana Souza; Torsoni, Marcio Alberto; Milanski, Marciane; Ignacio-Souza, Leticia M.; Simino, Laís Angélica; de Oliveira, Elaine; Lisboa, Patricia Cristina
Graphical abstract: Highlights: Coconut oil (CO) during lactation induces microRNAs alterations in adult offspring. CO exposure alters the lipid oxidation and synthesis, through miR-122 change. Lifelong exposure avoids the damage caused by exposure only during lactation. Abstract: We studied the molecular and epigenetic mechanisms associated with dysfunctions caused by postnatal coconut oil exposure. Lactating dams were divided into soybean oil (SO) and coconut oil (CO) groups (0.5 g/kg/gavage). Half of the CO offspring received CO in their chow throughout their lifetime (CO + C). Adult CO offspring had higher liver TRβ-1 mRNA, which is consistent with lower miR-181a and lower DIO2 mRNA in brown adipose tissue (BAT) and higher CPT-1 mRNA in white adipose tissue (WAT). CO + C offspring exhibited higher BAT miR-382*, but DIO2 was unaltered. This group also had higher liver SCD1, miR-122 expression, and WAT SCD1 mRNA. CO and CO + C offspring had lower hepatic CPT-1 mRNA. The disturbances in CO offspring may be partially attributed to alterations in the enzymes involved in lipid metabolism, which may be mediated via mechanisms associated with miR-122. Continuous exposure to CO prohibits some of these changes.